2020
DOI: 10.4314/jasem.v24i9.9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of <i>Azadirachta indica</i> A. Juss (Neem) Seed Oil in Controlling Wood Termite

Abstract: The protection of wood against biodeteriorating agents like termite during processing or in service has call for serious possible approach using new safer, environmental friendly preservatives hence this study therefore evaluated Azadirachta indica seed oil against termite attack on Gmelina arborea and Triplochiton scleroxylon wood. The seed oil was obtained using a soxhlet apparatus and N-hexane as the solvent. The wood was dimensioned into 20x20x20 mm and the seed oil was applied by brushing, dipping and soa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The absorption rate also shows that wood blocks absorbed the oil extract differently at varying concentrations indicating that the wood samples were easily impregnated with castor seed oil extract due to the low viscosity of the extract influenced by viscosity of the diluents, a result which agrees with the work of Adetogun (2011) while evaluating Cashew nut Shell Liquid Incorporated with Sodium Chloride (Table Salt) as Fungicide against Wood Decay. The mean absorption rate values were observed to be significantly different from each other as it increases with increase in concentration level The result obtained also agrees with the findings of Okanlawon et al, (2020b) who reported that absorption depends on the method of application, viscosity, soaking period and the level of concentration of the preservative. Mean with the same alphabet in each column are not significantly different from each other at α = 0.05.…”
Section: Absorption Of Preservatives Bysupporting
confidence: 88%
“…The absorption rate also shows that wood blocks absorbed the oil extract differently at varying concentrations indicating that the wood samples were easily impregnated with castor seed oil extract due to the low viscosity of the extract influenced by viscosity of the diluents, a result which agrees with the work of Adetogun (2011) while evaluating Cashew nut Shell Liquid Incorporated with Sodium Chloride (Table Salt) as Fungicide against Wood Decay. The mean absorption rate values were observed to be significantly different from each other as it increases with increase in concentration level The result obtained also agrees with the findings of Okanlawon et al, (2020b) who reported that absorption depends on the method of application, viscosity, soaking period and the level of concentration of the preservative. Mean with the same alphabet in each column are not significantly different from each other at α = 0.05.…”
Section: Absorption Of Preservatives Bysupporting
confidence: 88%